1998
DOI: 10.1046/j.1471-4159.1998.70010366.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding and Modulation of Cyclic AMP Levels Depend on the Chemical Nature of Residue 192 of the Human Cannabinoid Receptor 1

Abstract: The human cannabinoid receptor associated with the CNS (CB1) binds Δ9‐tetrahydrocannabinol, the psychoactive component of marijuana, and other cannabimimetic compounds. This receptor is a member of the seven transmembrane domain G protein‐coupled receptor family and mediates its effects through inhibition of adenylyl cyclase. An understanding of the molecular mechanisms involved in ligand binding and receptor activation requires identification of the active site residues and their role. Lys192 of the third tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 23 publications
(26 reference statements)
7
64
1
1
Order By: Relevance
“…6B) These results suggest that K3.28(192) is important to the binding of SR141716A at WT CB1, but this residue is not important to the binding of VCHSR at WT CB1. Residue K3.28(192) has previously been shown to be a very important residue for agonist binding at CB1 (Song and Bonner, 1996;Chin et al, 1998). The results reported herein are the first demonstration that this residue is also important for inverse agonist binding at CB1.…”
Section: Ligandsupporting
confidence: 62%
“…6B) These results suggest that K3.28(192) is important to the binding of SR141716A at WT CB1, but this residue is not important to the binding of VCHSR at WT CB1. Residue K3.28(192) has previously been shown to be a very important residue for agonist binding at CB1 (Song and Bonner, 1996;Chin et al, 1998). The results reported herein are the first demonstration that this residue is also important for inverse agonist binding at CB1.…”
Section: Ligandsupporting
confidence: 62%
“…Lys3.28(192) was used as the primary interaction site in CB 1 docking studies of HU210 and CP55,940 reported here based upon the K3.28(192)A mutation results of Song and Bonner (1996) and supported by subsequent studies (Chin et al, 1998). These studies showed a complete loss of HU210 and CP55,940 (but not WIN 55,212-2) binding and a Ͼ100-fold increase in EC 50 value for receptor activation upon this mutation.…”
Section: Modeling Studiesmentioning
confidence: 85%
“…Computational and mutational studies have identified several key amino acid residues in discrete noncontiguous regions of the TMHs that contribute in forming ligand binding sites (Abood, 2005;Reggio, 2005). These include but are not limited to the Lys3.28 (192), involved in the binding of anandamide, CP55,940, HU210, and SR141716A but not WIN55,212-2 (Song and Bonner, 1996;Chin et al, 1998;Hurst et al, 2002) via a hydrogen bonding interaction with the ligand. An aromatic microdomain contributed by Phe3.36,Trp4.64,Tyr5.39,Trp5.43,and Trp6.48 is involved in the binding of WIN55,212-2 and SR141716A (McAllister et al, 2002(McAllister et al, , 2003(McAllister et al, , 2004.…”
mentioning
confidence: 99%
“…Two endocannabinoid agonist analogues, arachidonyl-2-chloroethylamine (ACEA) and (R)-(+)-methanandamide, which are believed to share some of the same receptor contact points as CP55940 and HU-210 (22), were also tested; the T210I receptor was found to have a 3-4-fold enhancement in affinity for these ligands relative to that of wild-type CB 1 ( Table 1). The aminoalkylindole, (R)-(+)-WIN55212-2, is thought to have contact points with the receptor different from those of the compounds mentioned above, as shown by both modeling studies (35) and mutagenesis studies (26). Regardless, the T210I receptor displayed a similar change in its affinity for (R)-(+)-WIN55212-2 ( Table 1).…”
Section: Mutations At Position 210 Of Cb 1 Results In Shifts In Agonismentioning
confidence: 99%